ANALISIS PENGENAAN PAJAK PENGHASILAN TERHADAP YOUTUBER DAN SELEBGRAM - Septina Vera Wijayanti (Politeknik Keuangan Negara STAN, 2022)
Entertainment continues to change along with technological developments. People will always need entertainment in their spare time. Coupled with the Covid-19 pandemic, all activities must be carried out online from home. Youtube is a platform that contains various kinds of video content ranging from music, movies, to podcasts. Youtubers use this opportunity to earn money by creating content that people are interested in. Instagram is also a rising photo and video sharing social media platform. Selebgram (Instagram celebrities) earn income from promoting products. The purpose of this study is to analyze the imposition of income tax from each type of income earned by youtubers and celebrities. The method used in this study is a qualitative method. The results of this study indicate that youtubers and celebrities earn several types of income, namely from google adsense, brand deals/product placements, merchandise sales, professional speakers, patreon, paid endorsements, and paid promote. Each type of income is subject to different articles and rates based on the Income Tax Law. All of these incomes are objects of income tax that have the potential to increase state revenues.